Effect of ultrasonic vibration on the mechanical properties of 3D printed acrylonitrile butadiene styrene and polylactic acid samples - Maidin, Shajahan; Rajendran, Thavinnesh Kumar; Md Nor Hayati, Norilani; Yap, Yeong Sheng; Ismail, Shafinaz; Muhammad, Ahmad Hilmi (Elsevier Ltd, 2023)
Fused deposition modeling (FDM) is an extrusion-based AM process that is widely used due to its cost-effectiveness and user friendly. However, FDM also has some limitations such as the appearance of seam lines between layers and the production of excess material residue leading to poor surface finish, poor bonding between layers and porosity. This paper presents the findings on the application of ultrasonic vibration in an open-source FDM 3D printer to investigate its effect on the mechanical properties and microstructure of acrylonitrile butadiene styrene (ABS) and Polylactic Acid (PLA) samples. Two units of ultrasonic piezoelectric transducer were clamped horizontally on the surface of the 3D printer platform. The ultrasonic vibration was transmitted directly to the platform while the sample received vibration with a specific frequency while the printing process commences. Two process parameters, namely build orientation and ultrasonic vibration were selected to analyze their significance and optimization on the mechanical properties and the microstructure of the printed samples. High compressive and low surface roughness are required to have the best properties for the printed sample. Therefore, the optimization parameters are performed with these settings where the compressive strength is maximized and the surface roughness is minimized. The result shows that the overall compressive strength in ABS and PLA samples created in the Z-axis orientation is higher than in the X-axis orientation. However, the compressive strength of ABS and PLA samples is not much different after the ultrasonic vibration was applied during the printing process. The microstructure analysis shows that bonding between the layers is similar when applying ultrasonic vibration for both ABS and PLA samples. Furthermore, the result indicates that the surface roughness increased at 10 kHz and then decreased or became smoother at 20 kHz for both ABS and PLA material samples. The analysis shows that the build orientation significantly affects the compressive strength in ABS and PLA samples. However, the ultrasonic vibration has no considerable impact. In surface roughness, the build orientation and ultrasonic vibration significantly affect ABS samples. However, the PLA samples are only slightly affected. The optimum parameters for both materials are found where Zaxis orientation and 0 kHz of the ultrasonic vibration samples gave the best compressive strength and surface roughness value.